Determinants of Health Seeking Behaviour among Typhoid Fever Patients in Buea Health District, Cameroon - Kunlohmi, Gansey Carine (Advances in Social Sciences Research Journal, 2025)
Despite the availability of effective biomedical treatments, typhoid fever remains endemic in Buea Health District, Cameroon, underscoring a critical gap between disease awareness and health-seeking behavior (HSB). This article aimed to examine how knowledge of typhoid transmission influences HSB among residents with typhoid symptoms in Buea Health District. Guided by Avedis Donabedian’s Theory of Healthcare Quality, which postulates that the quality of care is determined by the interrelationship between healthcare structures, processes, and outcomes, the study explored how system-level and individual factors shape decisions to seek medical treatment. Methodologically, a quantitative cross-sectional survey was conducted among 150 adults selected through systematic sampling in selected health facilities. Data were collected using structured questionnaires and analysed using descriptive statistics and multiple linear regressions. Findings revealed that demographic factors, particularly age, significantly influenced HSB, with individuals under 30 years comprising 68.7% of respondents and demographic variables showing a strong positive relationship with care-seeking (β = 0.064, p = 0.003). Conversely, socio-economic factors such as income and occupation, while positively correlated, were not statistically significant predictors (β = 0.031, p = 0.355). Although 61.3% of respondents correctly identified contaminated water as a transmission route and 50% linked typhoid to poor sanitation, knowledge of transmission showed no significant impact on HSB (β = 0.012, p = 0.732). The model explained 45.3% of the variance in HSB (R² = 0.453). These findings imply that health interventions in Buea should shift from generalised education to demographically focused strategies. It is recommended that public health policy prioritize youth-centered outreach including mobile clinics, peer education, and digital campaigns; to improve timely and appropriate health-seeking behaviors.